An Analysis of Nutritional Status of Women in India: A Study of NFHS-4 - Kapur, Dr Bharti (The journal of contemporary issues in business and government, 2021)
One of the most significant challenges facing humanity is to eliminate hunger and malnutrition. The conditions of malnutrition and other diseases associated with it are mainly caused by consuming too much of food, consuming too little food, or consuming an unbalanced diet that is devoid of essential nutrients required by the body.Adequate nutritional attainment has a pivotal role in human well-being, especially for women because it has serious implications for the health of their children. The present paper is an attempt to analyze the level of malnutrition among women in India. An inter-state comparison has also been made pertaining to women’s malnutrition. It also investigates into inter sector (i.e. rural-urban), social and economic inequalities pertaining to malnutrition among women in India.These issues have been addressed by analyzing the National Family Health Survey- (NFHS-4) data, 2015-16. It is essential to express, at the start, that the current paper has a constrained extension as it presents a fundamental factsheet on women’s lack of healthy sustenance in India and doesn’t give a clarification or talk about the reasons for the current degrees of ailing health among women in India.